2021
DOI: 10.1101/2021.04.14.21255448
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gender Differences in Health Protective Behaviors During the COVID-19 Pandemic in Taiwan: An Empirical Study

Abstract: Introduction Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection produces more severe symptoms and a higher mortality in men than in women. The role of biological sex in the immune response to SARS-CoV-2 is believed to explain this sex disparity. However, the contribution of gender factors that influence health protective behaviors and therefore health outcomes, remains poorly explored. Methods We assessed the contributions of gender in attitudes towards the COVID-19 pandemic, using a hypo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
2
5
1
Order By: Relevance
“…Unlike a few previous studies that showed females having better preventive behavior, 27 , 28 we did not find any difference between males and females in this regard.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike a few previous studies that showed females having better preventive behavior, 27 , 28 we did not find any difference between males and females in this regard.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, the feeling of exhaustion suffered by women leaves them with a similar general boredom and demotivation regarding COVID-19-related information overload as with men; nevertheless, these feelings of pandemic exhaustion and the chronic nature of strict prevention measures leave men with higher demotivation to follow the PB than for women. These results are congruent with previous studies that women adopt more PB related to COVID-19 prevention [22][23][24], and thus they support the external validity of the PFS. This gender difference in the COVID-19 PB could be explained by the differential socialization experienced by men and women, in which women are usually socialized to be more self-protection oriented [25] and more obedient and disciplined [34].…”
Section: Invariance Of the Scalesupporting
confidence: 91%
“…Thus, analyzing the differential gender impact on psychological adjustment to the pandemic situation seems to be essential, as is studying the gender differences in PF in the face of the different phases of the pandemic. Other studies have found that women usually adopt more PB oriented to preventing SARS-CoV-2 transmission [22][23][24], probably because women usually assign more relevance to health issues than do men [25]. In this sense, we expect that women will present lower levels of the neglect dimension of PF.…”
Section: A Gender Perspectivementioning
confidence: 75%
“…Women experienced higher levels of negative emotions and showed higher levels of concern about their social life and the economy compared to men. In alignment with the recent literature (e.g., [ 57 ]), women also showed higher compliance with containment rules and greater engagement in online actions and prosocial behaviors than men.…”
Section: Discussionsupporting
confidence: 89%